Editorial - Loyiso Jita (Perspectives in Education, 2016)
From text: Many of the articles published in our 2016 edition have focused on the issue of quality education from a number of different perspectives. The current issue continues this journey and exploration but focuses more closely on three important aspects of the quality education debate: first, the focus is on higher education. Zeroing in on two professional programmes, one for teachers and another for engineers, several of the articles probe pertinent questions about the graduates’ knowledge, competences and attributes.